El desarrollo regional en Colombia, aportes para la sostenibilidad ambiental (2012)
The endogenous potential of a region, in terms of local knowledge or own biophysical and cultural conditions, is the foundation for the establishment of regional development models that can ensure environmental sustainability. e invaluable richness of Colombian nature and culture could be used to improve the living standards of its citizens. However, despite this, the country faces numerous restrictions such as war, drug dealing and economic recession, which prevents sustainable regional development. Nevertheless, those restrictions can motivate changes and the willing to search for general welfare.